REIMAGINING THE DIGITAL ORACLE: AN AFRICAN PHILOSOPHICAL AND THEOLOGICAL CRITIQUE OF ARTIFICIAL INTELLIGENCE - Bukola Abosede Folaranmi; Moses Adeolu Agoi; Zohaib Hassan Sain; Shazadi Hina Sain; Aulia Luqman Aziz (jfpublisher, 2025)
The emergence of artificial intelligence (AI) as a source of insight invites its characterization as a